World Investment Report 2022 - United Nations Conference on Trade; Development (United Nations, 2022)
The World Investment Report 2022 provides the latest trends and prospects for foreign direct investment. It documents the recovery of cross-border investment flows after the pandemic shock, looking at greenfield investment in industry, project finance in infrastructure, and international production activities of the largest multinationals. The Report also reviews recent policy developments, including trends in national investment policy measures and international investment agreements. It presents an overview of international corporate taxation and national investment incentive schemes worldwide. The theme chapter of the Report examines the implications for investment and investment policies of ongoing reforms in international taxation, including the adoption of a global minimum tax for multinationals and other mechanisms to counter harmful tax practices. It looks at the overall expected impact on cross-border investment flows, with a specific focus on developing countries, and assesses the effect on the use of common investment promotion tools such as fiscal incentives, special economic zones, and regional cooperation frameworks. The Report has a dedicated chapter on the global trends in financing for sustainable development. It presents key findings and policy implications for the consideration of the General Assembly of the United Nations.